N-(2-Bromo-4-methylphenyl)-2-(5-methyl-2-phenylpyrazolo[1,5-a]pyrimidin-7-yl)acetamide - Bassoude, Ibtissam (International Union of Crystallography, 2013)
The fused pyrazole and pyrimidine rings in the title compound, C22H19BrN4O, are almost coplanar, their planes being inclined to one another by 2.08 (13)°. The dihedral angles formed by the mean plane of the fused ring system and the phenyl and benzene rings are 16.21 (4) and 82.84 (4)°, respectively. An intramolecular N—H⋯N hydrogen bond is observed. In the crystal, molecules form inversion dimers via pairs of C—H⋯O hydrogen bonds. π–π interactions, with centroid–centroid distances of 3.4916 (9) Å, connect the dimers into a three-dimensional network.